2021
DOI: 10.1038/s41467-021-22339-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices

Abstract: Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Genetic studies for CHD have focused primarily on the autosome; a study of X chromosome genetic variation in >500 000 individuals found common alleles on chromosome Xq23 to be strongly associated with lower TC, LDL-C, and triglycerides in both females and males and associated with a reduced odds for CHD and type 2 diabetes. 36 ORs for CHD and type 2 diabetes for each rs5942634-T allele, the lead cholesterol-lowering variant in chromosome Xq23, were 0.98 (95% CI, 0.96–0.99) and 0.97 (95% CI, 0.96–0.99), respectively.…”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angina Pe...mentioning
confidence: 99%
“…Genetic studies for CHD have focused primarily on the autosome; a study of X chromosome genetic variation in >500 000 individuals found common alleles on chromosome Xq23 to be strongly associated with lower TC, LDL-C, and triglycerides in both females and males and associated with a reduced odds for CHD and type 2 diabetes. 36 ORs for CHD and type 2 diabetes for each rs5942634-T allele, the lead cholesterol-lowering variant in chromosome Xq23, were 0.98 (95% CI, 0.96–0.99) and 0.97 (95% CI, 0.96–0.99), respectively.…”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angina Pe...mentioning
confidence: 99%
“…The Amish cohort had a higher-than-average concentration of LDL-C (140 [SD 43] mg/dL) and HDL-C (56 [SD 16] mg/dL) as well as lower TG (median 63 [IQR 50] mg/dL) consistent with the known founder mutations in APOB and APOC3 7 , 8 , 14 . In the Women’s Health Initiative (WHI) cohort, the TC (230 [SD 41] mg/dL) and TG (median 129 [IQR 87] mg/dL) concentrations were higher than for other cohorts as previously described 12 . We accounted for lipid-lowering medications and fasting status and inverse rank normalized the phenotypes as before 12 , 14 which are further detailed in the Methods.…”
Section: Resultsmentioning
confidence: 64%
“…In the Women’s Health Initiative (WHI) cohort, the TC (230 [SD 41] mg/dL) and TG (median 129 [IQR 87] mg/dL) concentrations were higher than for other cohorts as previously described 12 . We accounted for lipid-lowering medications and fasting status and inverse rank normalized the phenotypes as before 12 , 14 which are further detailed in the Methods. The adjusted normalized lipid concentrations for the four lipids were similar across the cohorts.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations